(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
This research looks at the components that help to understand the text, or change it from just successive words to sentences of interest. It is not the benefit that a good word for grammar can be used for, but the benefit that the text producer reaches to the maximum limits of understanding when the recipient achieves the minimum level of understanding. At the very least, speech consists of sounds and letters, so words are sentences, sentences are made up of structures, these structures or components have a role without which the sentences are not straightforward. Synthetic, and some of them deviate from the structural or internal existence in the text to being outside the text. In this research we review the components that are characterized as external, unaware of hearing or perceptible with sight, but have their presence that is not straightforward and the textual structure is not complete without it.